Increasing Repurchase Intention Through Experiential Marketing and Customer Satisfaction - Lena Ellitan (CV. Ulil Albab Corp, 2022)
Marketing activities have now begun to focus on customer satisfaction. Knowing the factors that cause customers to be satisfied that can lead to repurchase intentions. This paper focuses on the discussion that experiential marketing can be a strategy that can be used by restaurant marketers to increase customer satisfaction and repurchase intention. This article is expected to add insight, and become a reference for now and in the future, especially in the field of marketing management regarding experiential marketing, customer satisfaction, and repurchase intention. Tt can be concluded that the higher the sense of experience, the higher the customer satisfaction, this phenomenon can occur because all businesses that focus on products and services aim to provide a pleasant experience to customers. When customer satisfaction increases, it can increase repurchase intention. Furthermore, the higher the customer satisfaction, the higher the repurchase intention.